Warehouse Threats and Loss Prevention Management in Case of Fire. (2016) - Balan, Ioana Lorena; Cioca, Lucian-Ionel; Torretta, Vincenzo; Talamona, Luca
Abstract: Warehouses play an important role when it comes to the reception, delivery and storage of various types of goods. Due to the complex scenarios that may occur, as well as the heterogeneous nature of goods, warehouses bear a higher risk of accidents. Regardless if we're taking about removing hassle or standardizing operations we speak the same language: insuring efficiency and increased efficiency leads to smart cost maintenances. In the article hear by we will observe the behavior of different warehouse materials in the case of trigger fired. Starting from the results obtained during the low scale tests and completing the premises with the large scale experiment (warehouse scale), we can get to a series of useful observations.